Abolir el binarismo. Femimutancia y la historieta argentina transfeminista - Laura Caraballo (Caravelle)
Transfeminist struggles in Argentina and Latin America within the context of their sociopolitical reality, have a correlation with visual narratives. Comics don’t only represent what is at stake in thought and activism, but also redefine themselves, finding their own anti-hegemonic logics of operation. Femimutancia’s comics allow us to approach certain ideas in which transfeminisms of the south are anchored, which are articulated in slogans heard in the streets and read in social media: «no transvestite, no feminism», «the personal is political».... The production of this non-binary author help us to explore the theoretical bases of these political slogans, elaborated by certain referents of the movement, such as Judith Butler, Simone de Beauvoir and Carol Hanisch.